Overall athlete well-being states in Japanese elite athletes via a national survey - Kinugasa, T.; Noguchi, Y. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: It appears that the optimization of athlete well-being has received considerable attention in academic and practical fields of high performance sport. The International Olympic Committee has promoted the importance of athlete well-being particularly focused on mental health (Reardon et al., 2019). Nevertheless, the literature is limited to understand the case of Japanese athletes. Therefore, the aim of this study was to conduct a fact-finding national survey of athlete well-being in Japan.